Somebody to Lean On: The Moderating Effect of Relationships on Links Between Social Withdrawal and Self-Worth. (17th June 2019) - Clifford, Brandon N.; Nelson, Larry J.
Abstract: Previous research has discovered different subtypes of social withdrawal based on motivations to approach or avoid social interactions. Each of these motivations are uniquely related to indices of maladjustment during emerging adulthood, including aspects of the self. However, research has yet to investigate whether or not relationship quality moderates these associations. The purpose of this study was to examine whether relationship quality with best friends, romantic partners, mothers, and fathers, respectively, serve as protective factors in the negative links between shyness and avoidance and self-worth. The participants included 519 college students ( M age = 19.87, SD = 1.99, 61% female) from four universities across the United States. Results revealed that relationship quality with both best friends and romantic partners moderated the relation between shyness and self-worth. The differences between parent and peer relationships are discussed.